The prognostic value of extramural venous invasion in colorectal carcinoma - Mirjana Ćuk; Slavica Knežević Ušaj; Ištvan Klem; Radoslav Gajanin; Danijela Batinić Škipina; Radmil Marić; Sanja Marić; Nenad Lalović; Nikolina Dukić (Биомедицинска истраживања, 2020)
Introduction: Extramural venous invasion (EMVI) is a significant predictive factor of the prognosis for patients with colorectal carcinoma and it is directly connected with the relapse of a disease, especially with the appearance of distant metastases. Methods: The research comprises 90 patients with colorectal cancer. Representative samples of tumor tissues obtained by surgical resection are fixed in 4% formalin and embedded into paraffin blocks. Semi-series incisions of 4?m thickness were stained by HE method and Van Gieson’s method. Results: Out of 90 analyzed patients, 21 (23,33%) were with EMVI, and 69 (76.67%) without EMVI on the histological preparations stained by HE method. EMVI was found in 7 more tumors on the preparations stained by Van Gieson’s method. Sensitivity of the method determining EMVI on the histological preparations stained by Van Gieson’s method was better for 25% (7/28) than on the preparations stained by HE method. EMVI was not found in patients at A and B1 stage of disease according to Astler- Coller classification, but out of 77 patients which were at B2, C1 and C2 stage EMVI was found in 28 (36,36%) patients, p?0,01. EMVI was found in 18/77 (23,38%) patients who had a tumor of low histological gradus, p?0,01 and in 10/13 (76,92%) patients who had a tumor of high histological gradus, p?0,01. In patients with neural invasion, EMVI was found in 18/22 (81,82%), whereas in patients without neural invasion EMVI was found in 10/68 (14,71%), p?0,01. In patients with weak intensity of peritumoral lymphocytic reaction EMVI was found in 20/41 (48,78%) whereas in patients with moderate and noticeable level it was found in 8/49 (16,33%), p?0,01. There was a significant correlation between extramural venous invasion and other parameters of unfavorable prognosis. Conclusion: EMVI is an important indicator in administration of postoperative adjuvant therapy in patients with colorectal carcinoma. A special histochemical method of elastic fiber stain should be applied in everyday practice when EMVI is not found on HE stained preparations in patients with CRC.
Keywords: colorectal carcinoma; extramural venous invasion; elastic fibre stain